Accumulation of selenium its antioxidant properties in plants, animals and humans - Ghritlahre, S K; Kumar, Awadhesh; Yadav, M K; S, Aravindan (Indian Farming, 2018)
Drought results in production of reactive oxygen species in stressed plants, which causes oxidative damage to the cellular constituents such as carbohydrates, lipids, nucleic acids and proteins, ultimately reducing plant growth, respiration and photosynthesis. Application of selenium reduces the oxidative damage by production of compatible solutes. The accumulation of these organic solutes prevents cellular dehydration and helps the plants to retain water in cells. Another role of selenium is to improve drought tolerance in crop plants and protect them from oxidative stress by stimulating senescence to produce ROS-scavenging enzymes. Selenium increases SOD and GPX activities, thus activating the protective mechanisms against oxidative stress.